Virgil's elements : physics and poetry in the Georgics - Ross, David O. (Princeton legacy library., 1987)
Professor Ross presents the Georgics as a poem of science, of the power and ultimate failure of knowledge. Exploring the science that Virgil knew and used, he analyzes the oppositions and balances of lire and water, of the qualities of hot and cold, wet and dry, throughout the poem. These the farmer manipulates to create the balance necessary for growth, yet, in Virgil's universe, the potential for destruction inevitably results in a profound pessimism. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.